2015
DOI: 10.1136/annrheumdis-2015-eular.1154
|View full text |Cite
|
Sign up to set email alerts
|

THU0517 Invasive Fungal Infections Survey in 852 Childhood-Onset Systemic Lupus Erythematosus: A Multicenter Cohort

Abstract: BackgroundThe majority of infections in childhood-onset systemic lupus erythematosus (cSLE) patients are caused by virus and bacteria, and less frequently by opportunistic agents, such as fungi.1 However, studies evaluating solely invasive fungal infections (IFI) in cSLE patients are restricted to case reports or case series1 without any systematic evaluation of the possible associated risk factors and outcomes in pediatric lupus population.ObjectivesTo study the prevalence, risk factors and mortality of IFI i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Lymphopenia (<1500 cells/mm 3 ) and leukopenia (white blood cell count <4000/mm 3 ) at cSLE diagnosis occur in 43% and in 27%, respectively, and may be associated with disease activity, drug therapy, and current infections [1,3,8,10]. Autoimmune hemolytic anemia and immune thrombocytopenia (<100,000/mm 3 ) may be the initial presentation and occur at cSLE diagnosis in 21% and 15%, respectively [10].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Lymphopenia (<1500 cells/mm 3 ) and leukopenia (white blood cell count <4000/mm 3 ) at cSLE diagnosis occur in 43% and in 27%, respectively, and may be associated with disease activity, drug therapy, and current infections [1,3,8,10]. Autoimmune hemolytic anemia and immune thrombocytopenia (<100,000/mm 3 ) may be the initial presentation and occur at cSLE diagnosis in 21% and 15%, respectively [10].…”
mentioning
confidence: 99%
“…The most important risk factors associated with infections at cSLE onset are related to this systemic disease (leukopenia, neutropenia, lymphopenia, disease flare, and hypocomplementemia), concomitant primary immunodeficiency syndrome, and immunosuppressive treatment [1]. The most frequent infection sites in cSLE patients are skin and soft tissue, pneumonia, and urinary tract infections [1,8]. A recent study reported invasive fungal infections in 33 of 852 (3.9%) cSLE patients, particularly candidiasis and invasive aspergillosis.…”
mentioning
confidence: 99%
See 3 more Smart Citations